Удосконалення роботи сортувальної гірки як ланцюга перевізного процесу - Калашнікова, Татьяна Юріївна; Костяк, Анна Йосипівна (НТУ "ХПІ", 2015)
Проаналізовано основні проблеми у роботі сортувальної гірки. Для скорочення тривалості затримок при виконанні операцій гіркового циклу запропоновано: збільшення швидкості заїзду та насуву гіркового локомотива; скорочення часу розпуску за рахунок спорудження спеціальної колії для вагонів, які не підлягають розпуску з гірки звичайним способом; скорочення тривалості осаджування составів на коліях сортувального парку за рахунок збільшення частки підтягувань вагонів з боку хвостової горловини сортувального парку; проведення додаткових занять з операторами гальмових позицій; збільшення кількості робітників.

It analyzes the main problems in the yard and slides, as chains of transportation process. An increase of idle cars with recycling. The aim of the article is to develop measures to reduce the duration of a cycle hump, as a component of the total downtime of the car, in order to ensure its reduction, in turn, will reduce operating costs and improve the competitiveness of rail transport compared with other modes of transport. To reduce the length of delays in the operations cycle hump suggested: increasing the speed of arrival and sliding hump locomotive; reducing the time of dissolution by building a special way for the cars are not subject to dissolution with slides in the usual way; reduction of deposition of compositions in the ways of sorting the park by increasing the share of cars pull-ups on the part of the caudal neck sorting park; holding extra classes with the operators of the brake positions; increasing the number of workers.
Improvement of work of sorting hill as chains of vehicular process
Keywords: залізничний транспорт; сортувальна станція; простій вагонів; логістичний підхід; railway transport; marshaling hump; marshalling yard; simple wagons; logistical approach